Edukasi Pemilahan Sampah dan Pengolahan Sampah Organik Menjadi Kompos di SMAN 1 Tinambung - Putera, Alexander Kurniawan Sariyanto; Isdaryanti, Isdaryanti; Rahmah, Mufti Hatur (Universitas Sulawesi Barat, 2024)
Education on waste separation and management in high schools is a crucial initiative to implement. High school students possess a high level of awareness, making them potential agents of education within their communities. This community service project aims to provide knowledge on various waste separation techniques, waste processing products, and the importance of the waste management process. The project employed discussion and case method techniques to effectively enhance the understanding of students at SMA 1 Tinambung. Based on the evaluation results, the project demonstrated an increase in students' knowledge and awareness regarding waste separation and management, both in the school environment and their surroundings. Additionally, this project was highly engaging for the students, as it was both enjoyable and introduced waste-based products that they had never encountered before. Therefore, this initiative has made a positive contribution to the students of SMA 1 Tinambung.